The Effect of Non-Performing Loan (NPL) on Net Income at PT Bank Central Asia Tbk - Christopher Chandra, Jhonathan; Elvina Putri, Anastasia; Zefania Ongko, Adrianus; Tiur Manurung, Elizabeth (Politeknik Negeri Jakarta, 2025)
The purpose of this study is to analyze the effect of non-performing loan on net income for the period 2016 (Q3 and Q4) - 2024 at PT Bank Central Asia Tbk. NPL is a loan that no longer brings any profit to the financial institution, because the borrower has failed to pay the principal and/or interest on time. Thus, the NPL level shows the financial health of bank and the quality of its loan portfolio. The data used is from the company’s quarterly financial statement from the period 2016 (Q3 and Q4). The authors used the linear regression method to test the relationship between two variables, which are non-performing loan as an independent variable and net income as a dependent variable. Regression results show that non-performing loan has a significantly positive impact on net income, with a coefficient 1.0272 and p-value 0.0371. It means that every one unit increase in non-performing loan will increase net income by 1.0272. Keywords: Non-Performing Loan; Net Income; PT Bank Central Asia Tbk; Linear Regression